2010
DOI: 10.1016/j.neuropsychologia.2010.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive changes as a result of a single exposure to placebo

Abstract: Placebo has been shown to be a powerful analgesic with corresponding reduction in the activation of the pain matrix in the brain. However, the response to placebo treatment is highly variable. It is unclear how anticipatory and pain-evoked potentials are affected by the treatment and how reproducible the response is. Laser stimulation was used to induce moderate pain in healthy volunteers. We induced placebo analgesia by conditioning subjects to expect pain reduction by applying a sham anaesthetic cream on one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 33 publications
2
28
0
2
Order By: Relevance
“…The current study used the Chinese version of LOT-R (Life Orientation Test-Revised) [39, 40] to assess participants’ levels of dispositional optimism [2, 12]. The LOT-R includes 10 items that evaluate generalized expectancies for either positive or negative outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study used the Chinese version of LOT-R (Life Orientation Test-Revised) [39, 40] to assess participants’ levels of dispositional optimism [2, 12]. The LOT-R includes 10 items that evaluate generalized expectancies for either positive or negative outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Although extreme optimism can be harmful as it can promote an underestimation of risk and poor planning [6, 7], moderate optimism can motivate adaptive behavior in the present towards a future goal [7], and is beneficial to both physical and psychological wellbeing [810]. Optimists tend to have lower self-reported depressive symptoms [11], whereas pessimists report more negative expectations of the future [1214]. Additionally, optimists were observed to have a lower risk of cardiovascular disease compared with pessimists [11, 15], and to be associated with lower incidence rate of complications and better recovery after surgery[16].…”
Section: Introductionmentioning
confidence: 99%
“…Following this placebo administration, this instruction is often reinforced by lowering stimulus intensity (unbeknown to the participant), leading the participant to experience actual relief and attribute it to the placebo (e.g. Atlas et al, 2010; Colloca et al, 2010; Geuter et al, 2013; Koban et al, 2012; Morton et al, 2010; Price et al, 1999; Wager et al, 2004). Despite an important involvement of learning in placebo (Colloca and Benedetti, 2009; Schafer et al, 2015), suggestions are central to placebo and nocebo effects, and can be effective even alone, i.e.…”
Section: Social Information Effects On Pain and Emotionmentioning
confidence: 99%
“…Some recent studies adopting a pharmacological conditioning with drugs such as morphine (Amanzio and Benedetti, 1999; Benedetti et al, 2007), immunosuppressor cyclosporin A (Goebel et al, 2002; Pacheco-Lopez et al, 2009), dopamine-agonist apomorphine (Benedetti et al, 2004), benzodiazepine receptor agonist midazolan and antagonist flumazenil (Petrovic et al, 2002), found that the conditioned placebo responses mimic drug effects, thus providing evidence that an important factor in eliciting bodily placebo responses is the previous exposure to effective treatment. Conditioned placebo analgesic responses not only appear sensitively shaped by prior exposure to treatment effectiveness (Colloca and Benedetti, 2006; Morton et al, 2010b; Morton et al, 2010a), but also by the number of learning trials (Colloca and Benedetti, 2006; Colloca et al, 2008a; Colloca et al, 2008b; Colloca and Benedetti, 2009; Colloca et al, 2010; Colloca and Miller, 2011).…”
Section: Psychological Mechanisms Of the Placebo Effect: Contributionmentioning
confidence: 99%
“…Importantly, higher empathy yielded stronger placebo responses, supporting a link between the ability to modify behaviors following social observational learning and empathy. Beyond empathy, some other dispositional traits such as altruism (Mackenbach, 2005) and optimism (Geers et al, 2005; Geers et al, 2010; Morton et al, 2010b) seem to play a role, indicating that emotions and personality traits modulate expectations and placebo-induced behavioral changes.…”
Section: Psychological Mechanisms Of the Placebo Effect: Contributionmentioning
confidence: 99%